2012
DOI: 10.1002/ejic.201200746
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Origin for Multistability in a Photomagnetic CoFe Prussian Blue Analogue

Abstract: Keywords: Prussian blue analogues / IR spectroscopy / Multistability / Cobalt / Iron / PhotomagnetismSwitchable compounds attract growing interest, as they offer promising perspectives for high-density storage applications. Much effort has been invested in understanding the mechanisms involved in such properties, in order to prepare systems that are suitable for real applications. Compounds exhibiting an electronic transition that can be triggered by an external stimulus have been extensively studied. While mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(58 reference statements)
1
4
1
Order By: Relevance
“…At this stage, it is interesting to note that studies on photo-active Na 2 Co 4 [Fe(CN) 6 ] 3.3 •14H 2 O PBAs actually showed that the Na + undergoes a motion upon photoinduced electron transfer. 79 Further evidence of such motions has been found for the PBA of formula Cs 0.7 Co 4 [Fe(CN) 6 ] 2.9 •16H 2 O. At first glance, the remarkable photo-efficiency of this Cs-based PBA and its relatively high relaxation temperature could seem contradictory with our findings.…”
Section: ■ Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…At this stage, it is interesting to note that studies on photo-active Na 2 Co 4 [Fe(CN) 6 ] 3.3 •14H 2 O PBAs actually showed that the Na + undergoes a motion upon photoinduced electron transfer. 79 Further evidence of such motions has been found for the PBA of formula Cs 0.7 Co 4 [Fe(CN) 6 ] 2.9 •16H 2 O. At first glance, the remarkable photo-efficiency of this Cs-based PBA and its relatively high relaxation temperature could seem contradictory with our findings.…”
Section: ■ Discussioncontrasting
confidence: 76%
“…Beyond the changes in the distortion of the coordination sphere, other structural modifications could accompany the ETCST: a motion of the alkali ion induced by a modification of the local charges (and consequent changes in the A···π CN interactions), changes in the distortion of the cubic framework, and so forth. At this stage, it is interesting to note that studies on photo-active Na 2 Co 4 [Fe­(CN) 6 ] 3.3 ·14H 2 O PBAs actually showed that the Na + undergoes a motion upon photoinduced electron transfer . Further evidence of such motions has been found for the PBA of formula Cs 0.7 Co 4 [Fe­(CN) 6 ] 2.9 ·16H 2 O.…”
Section: Discussionmentioning
confidence: 86%
“…CoFe PBAs to characterize and control the electron transfer mechanism and the associated magnetic properties. [15][16][17][18][19][20][21][22][23][24][25] These fascinating photomagnetic properties were found to depend upon the nature and amount of alkali cations inserted in the structure 16,17,20,26 and a series of Rb 2 Co 4-x Zn x [Fe(CN) 6 ] 3.3 PBAs with different stoichiometries has been studied to explore the photo-induced metastable state. 12,13,23 They also devoted a lot of efforts to the investigation of the Rb 2 Co 4 [Fe(CN) 6 ] 3.3 · 11 H 2 O PBA (called RbCoFe in the following), which was chosen as a model compound for the study of the photomagnetic effect because it combines a large photomagnetic effect and a reproducible synthesis.…”
mentioning
confidence: 99%
“…Thus, by applying an external stimulus, such as light [4][5][6], temperature [7,8] or pressure [9] on these compounds, it is possible to induce a charge transfer process in between the bimetallic pair which is accompanied by a change in the magnetic properties. Especially the CoFe PBA have been of particular interest in the past years [10][11][12][13]. During irradiation at low temperatures, the diamagnetic Co III (LS)-Fe II pairs are excited into a paramagnetic Co II (HS)-Fe III state and return to the initial state when the temperature is increased.…”
Section: Introductionmentioning
confidence: 99%